Vaccine-Induced Skewing of T Cell Responses Protects Against Chikungunya Virus Disease - Broeckel, Rebecca M.; Haese, Nicole; Ando, Takeshi; Dmitriev, Igor; Kreklywich, Craig N.; Powers, John; Denton, Michael; Smith, Patricia; Morrison, Thomas E.; Heise, Mark; DeFilippis, Victor; Messaoudi, Ilhem; et al. (Frontiers in Immunology, 2019)
Chikungunya virus (CHIKV) infections can cause severe and debilitating joint and muscular pain that can be long lasting. Current CHIKV vaccines under development rely on the generation of neutralizing antibodies for protection; however, the role of T cells in controlling CHIKV infection and disease is still unclear. Using an overlapping peptide library, we identified the CHIKV-specific T cell receptor epitopes recognized in C57BL/6 infected mice at 7 and 14 days post-infection. A fusion protein containing a mix of five of these MHC I and II T cell receptor epitopes (CHKVf5) was expressed using adenovirus and cytomegalovirus-vectored vaccines. Mice vaccinated with CHKVf5 elicited robust T cell responses to higher levels than normally observed following CHIKV infection, but the vaccine vectors did not elicit neutralizing antibodies. CHKVf5-vaccinated mice had significantly reduced infectious viral load when challenged by intramuscular CHIKV injection. Depletion of both CD4+ and CD8+ T cells in vaccinated mice rendered them fully susceptible to intramuscular CHIKV challenge. Depletion of CD8+ T cells alone reduced vaccine efficacy, albeit to a lesser extent, but depletion of only CD4+ T cells did not reverse the protective phenotype. These data demonstrated a protective role for CD8+ T cells in CHIKV infection. However, CHKVf5-vaccinated mice that were challenged by footpad inoculation demonstrated equal viral loads and increased footpad swelling at 3 dpi, which we attributed to the presence of CD4 T cell receptor epitopes present in the vaccine. Indeed, vaccination of mice with vectors expressing only CHIKV-specific CD8+ T cell epitopes followed by CHIKV challenge in the footpad prevented footpad swelling and reduced proinflammatory cytokine and chemokines associated with disease, indicating that CHIKV-specific CD8+ T cells prevent CHIKV disease. These results also indicate that a T cell-biased prophylactic vaccination approach is effective against CHIKV challenge and reduces CHIKV-induced disease.